(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The science of aruz has held a foundational place in classical Persian-Tajik poetics, evolving through centuries via concise treatises and integrated commentaries. One such lesser-known work is Muntakhab ul-aruz, which, despite its rich instructional content on poetic meters, remained outside scholarly attention until its recent rediscovery and publication by Urvatullo Toirov in 2007. Existing literature has failed to definitively establish the authorship and exact period of composition of this treatise, leading to contradictory conclusions and attributions, including incorrect association with Mawlana Nizamiddin of the 16th century. This study aims to critically reassess the historical, literary, and structural origins of Muntakhab ul-aruz, establish a more accurate chronology, and examine its scholarly significance in the context of 18th–19th century aruz studies. Through textual comparison with known works such as Mi’raj ul-aruz (1827), as well as analysis of embedded poetic examples from 16th-century authors like Urfi Shirazi and Nasirali Sarhindi, the research concludes that Muntakhab ul-aruz was composed in the second half of the 19th century by an unknown author. The article refutes previous assumptions of 16th-century origin and authorship, offering clear philological and intertextual evidence that repositions the treatise within a later historical framework. The findings contribute to a more accurate mapping of Persian-Tajik aruz scholarship, while reaffirming the instructional value of Muntakhab ul-aruz in modern poetic theory and pedagogical practice.